PENGARUH JARAK TANAM PADA PENGGUNAAN METODE BUDIDAYA RAKIT TALI TERHADAP BERAT RUMPUT LAUT (Eucheuma cottonii) DI DUSUN TOISAPU KECAMATAN LEITIMUR SELATAN - Etnah Garpenassy; H Tuaputty (Program Studi Pendidikan Biologi FKIP Unpatti, 2016)
Background: Toisapu village is one of village in Ambon Island which have potential to develop seaweed. Prospects Seaweed cultivation is very beneficial if growth and quality can be developed as a base for the production of various purposes in the industrial world. However, cultivation techniques undertaken by the local community have not fully had good planting quality. Method: The study includes the preparation phase, the implementation stage, and the observation stage. The parameters measured were the growth rate of Eucheuma cottonii seaweed is weight in the form of gram, using Completely Randomized Design (RAL) with 4 treatment levels and 6 replications. Results: The results of this study show that at a distance of 30 cm seaweed growth experienced a better growth rate when compared with other growth spacing, with wet weight for 45 days was 218 grams. Conclusion: Plant spacing affects the weight of seaweed, a good planting distance for seaweed growth is 30 cm at sea ebb and sea level with average wet weight for 45 days (6 weeks) is 218 grams.